PEDGOGICAL CONTENT KNOWLEDGE ANALYSIS OF BASIC SCIENCE BOOKS IN SCIENCE LEARNING CLASS III OF KUTA RENTANG STATE ELEMENTARY SCHOOL - Nurul Zikri Filina; Siti Mayang Sari; Zahraini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Elementary school teachers must understand the content of the material and how to teach it to students or known as Pedagogical Content Knowledge (PCK), and the books used as teacher guides must comply with the PCK principles. This research is descriptive research that aims to obtain information about the scope of Pedagogical Content Knowledge in the Basic Science books for class III SD Negeri Kuta Rentang. The research subject is the sub-chapter of the Basic Science book which is used for third grade students at SD Negeri Kuta Rentang. The book evaluation instrument contains aspects of Pedagogical Content Knowledge content in Basic Science books. Filling out the teacher's book evaluation instrument is done by giving a value of 0 to 5 on each aspect of the assessment. The data that has been obtained is analyzed by calculating the percentage value of Pedagogical Content Knowledge. Based on the results of the analysis of Pedagogical Content Knowledge (PCK) in science learning, Basic Science books are at a percentage of 94% with the very achieved category. However, this book should not be used as the only guide, teachers need to have other companion books as support and complements, especially on aspects of core knowledge and the metacognition framework.